Unit Hydrograph Analysis For Batang Sadong At Serian - Wan Mohamad Mirzan, Wan Hanapi (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Phenomenon of flood is commonly considered to be an unusually high stage of a river cause by excessive rainfall over certain duration of time. It may cause damage to life and property in the adjoining country. This study deals with estimating the flood discharge by using of Unit Hydrograph Method for given watershed in Sarawak. The theory of Unit Hydrograph is related to surface runoff phenomenon, which is considered even today as one of the most important contributions to hydrological studies. A Unit hydrograph is a discharge hydrograph resulting from one unit of excess rainfall uniformly falls over the watershed area at uniform rate during a specified period of time. In order to derive a unit hydrograph, a case study in Batang Sadong at Serian, in the Sarawak has been selected for analysis purposes. The catchment is located about 75 km from Kuching City, and its catchment area is 740 km2. Several isolated storms with different duration have been selected for deriving a representative unit hydrograph. Further study is still needed because the availability of hydrological data is still limited, hence more accurate analysis with longer period of data is needed. All the hydrological data required during analysis are provided by the Department of Irrigation and Drainage (D. I. D), Sarawak. ' Discussion about the data, analysis and the result that have been found is provided in this report.